2018
DOI: 10.1371/journal.pone.0198973
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control and counterintuitive science and maths reasoning in adolescence

Abstract: Existing concepts can be a major barrier to learning new counterintuitive concepts that contradict pre-existing experience-based beliefs or misleading perceptual cues. When reasoning about counterintuitive concepts, inhibitory control is thought to enable the suppression of incorrect concepts. This study investigated the association between inhibitory control and counterintuitive science and maths reasoning in adolescents (N = 90, 11–15 years). Both response and semantic inhibition were associated with counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 49 publications
7
35
1
1
Order By: Relevance
“…Further work will need to replicate this finding, which may reflect an advantage of a slower more deliberative approach to complex maths problems. Consistent with these results, a previous study in adolescents found that the ability to withhold a response on an inhibitory control Go/No-Go task was associated with longer RTs, suggesting more reflection, on science and math problems requiring counterintuitive reasoning (Brookman-Byrne, Mareschal, Tolmie, & Dumontheil, 2018). In the present study however science was not associated with processing speed.…”
Section: Discussionsupporting
confidence: 91%
“…Further work will need to replicate this finding, which may reflect an advantage of a slower more deliberative approach to complex maths problems. Consistent with these results, a previous study in adolescents found that the ability to withhold a response on an inhibitory control Go/No-Go task was associated with longer RTs, suggesting more reflection, on science and math problems requiring counterintuitive reasoning (Brookman-Byrne, Mareschal, Tolmie, & Dumontheil, 2018). In the present study however science was not associated with processing speed.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies showed that learners not only need to reconstruct their conceptual understanding, but also need to actively inhibit their misconceptions (Brookman- Byrne et al, 2018;Mason et al, 2019), because many misconceptions are difficult to eradicate and keep coexisting with newly acquired conceptions (Gelman, 2011;Legare and Visala, 2011;Shtulman and Lombrozo, 2016). For example, under time pressure, even professional scientists start to reveal intuitive misconceptions (Goldberg and Thompson-Schill, 2009;Kelemen et al, 2013;Shtulman and Harrington, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Two independent, but complimentary lines of inquiry may provide insights into possible mechanisms of these developmental differences. First, developmental theories emphasize reductions in impulsivity over adolescence, which are linked to the protracted development of prefrontal regions over the same developmental period (Bezdjian et al, 2014;Brookman-Byrne, Mareschal, Tolmie, & Dumontheil, 2018;Hallquist, Geier, & Luna, 2018;Steinberg et al, 2017). Second, computational theories of speed-accuracy trade-offs highlight that the time to arrive at a cognitive solution gives insights into the amount of evidence participants sample before deciding upon a solution (Fitts, 1966;Stone, 1960 tests, which have been used for decades, also arguably carry a higher likelihood of familiarity than novel items like MaRs-IB.…”
Section: Discussionmentioning
confidence: 99%